REPRESENTASI PERISTIWA DAN AKTOR DALAM KASUS FERDY SAMBO PADA KORAN TEMPO: ANALISIS WACANA KRITIS BERBASIS KORPUS - Elektra Aulia Maharani; Wagiati, Wagiati; Darmayanti, Nani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The murder case of Yosua Hutabarat involving high-ranking National Police officer Ferdy Sambo has attracted the attention of the public and the mass media, including Koran Tempo. This article aims to explain Koran Tempo's ideology by representing incident and actors featured in news stories about the Ferdy Sambo case in Koran Tempo using Norman Fairclough's critical discourse analysis and corpus-based approaches. The research results show that the news about the Ferdy Sambo case in Koran Tempo tends to side with the victim or Yosua Hutabarat. This can be seen from the large number of uses of passive sentences to represent the victim and active sentences to represent the perpetrator as the main actor in the murder. This article argues that using sentences and words in the media through formed discourse can construct reality and social phenomena and influence society to side with certain ideologies or values ​​espoused by the media.